Blue carbon storage in a sub-Antarctic marine protected area - Bergagna, Lucia (2024)
High‑latitude ecosystems have been overlooked in carbon budgets, which traditionally focus on mangroves, salt marshes, and seagrasses. The benthic assemblages and their Nature Contributions to People in Namuncurá – Burdwood Bank I and II, two offshore sub‑Antarctic Marine Protected Areas (MPAs), are the conservation values. Here we show that the carbon reservoirs of these MPAs can be greater than those of their Antarctic counterparts, which, together with their extension, emphasize the need to maintain their protected status. Considering their total area, these MPAs stored in biomass 52,085.78 Mg C, corresponding 34,964.16 Mg to organic carbon (OC) and 17,121.62 Mg to inorganic carbon (IC). Surficial sediments stored 933,258,336 Mg C with 188,089,629 Mg of OC and 745,168,707 Mg of IC. However, when accounting for CO2 production through CaCO3 precipitation, the IC fractions decrease to 3,150.37 Mg C and 137,111,042 Mg C for biomass and sediments, respectively. We assume low sediment deposition due to the oceanic location, as direct sedimentation rates for these areas are unavailable. Most blue carbon assessments have focused solely on OC, despite the formation of CaCO3 releases CO2, decreasing net carbon storage. We compared various approaches for incorporating carbonates into carbon estimations. These results underscore the importance of including IC into carbon assessments and highlights the importance of sub‑Antarctic benthic ecosystems as nature‑based solutions to climate change.